Language and Structure of a Business Email in the Conditions of Russian, Polish and English-language Communication - Rolak, Irina; Król-Kumor, Martyna (Respectus Philologicus, 2025)
This article offers a comparative analysis of Polish, Russian and English-language business emails. The results of the research displayed both similarities and differences in linguistic realisation of this genre of business communication. The greatest similarities were observed in those elements of an electronic letter, which are typical only for this particular form of correspondence. The differences are mainly in using para-linguistic devices, such as punctuation, discoursive-stylistic devices in writing upper- and lower-case letters, and in the linguo-cultural dependence in the implementation of such elements as the greeting and the closing formula. Polish and Russian emails are distinguished by a high degree of formality and a tendency to maintain an official tone compared to English-language texts of this genre, in which one can notice a greater directness and avoidance of literature, which is particularly characteristic of Polish courtesy formulas.Similarities detected in the comparative study may be due to adherence to netiquette, while differences are triggered by different norms in the etiquette of each language. This means that despite the universality of netiquette norms and the dominance of English in international correspondence, email still retains linguo-cultural specificity due to differences in ethnic worldviews and the officialdom of Slavic culture in relation to the openness of Euro-American civilisation.
Keywords: email pragmatics; linguistic etiquette; netiquette; linguistic confrontation; cross-cultural communication